How cities remember socialism?: the public spaces and ideology in Croatia - Potkonjak, Sanja (2007)
The paper discusses the transformation of the town of Sisak, Croatia during the 90's. It shows how imaginaries of the city materialize and “ embed in physical space” in order to fit ideological desires.